Penyakit Sel Sabit pada Pasien Laki-laki Berusia 27 Tahun yang Sebelumnya Didiagnosis sebagai Talasemia: Sebuah Laporan Kasus - Cahyanur, Rahmat; Kurniawan, Andree; Sharfina, Ratuafni; Mulansari, Nadia Ayu (UI Scholars Hub, 2023)
Sickle cell disease (SCD) is a hemoglobinopathy inherited in an autosomal recessive pattern arising from a mutation causing substitution of valine for glutamic acid in the sixth amino acid of the β-globin chain. The clinical manifestation of SCD varies from acute pain, chronic anemia, to multi-organ infarct and failure. SCD is known to be rare in Indonesia. However, we recently encountered a SCD patient presenting with recurrent pain and hypesthesia since a year ago. The diagnosis of SCD in this patient was established based on the results of peripheral blood smear and hemoglobin electrophoresis. The patient had previously been diagnosed with thalassemia at the age of 19 years old due to a history of icterus, thus delaying prompt treatment. This further emphasizes the challenges in distinguishing SCD, which is relatively rare in Indonesia compared to thalassemia, especially considering the complexity and the variability in the phenotypic presentation of SCD. The patient was then given supportive therapy consisting of blood transfusion and symptomatic treatment, as well as consideration to administer hydroxyurea if the patient’s clinical condition worsens.